Stakeholder identification methods used in private organisations' projects in Nigeria. Issue 2 (4th October 2021) - Olatunde, Nathaniel Ayinde; Awodele, Imoleayo Abraham; Odeyinka, Henry Agboola
Abstract : Purpose: The purpose of the study is to examine the stakeholder identification (SI) methods used in building projects procured by private corporate organisations in Southwestern Nigeria to draw a correlation between methods used for SI and project performance in the study area, thereby enhancing project performance. Design/methodology/approach: The study used a census survey to purposively select 30 projects managers (who indicated from a first-stage questionnaire) that they have participated in structured stakeholder management (SM) from a list of 106 project managers and client representatives who have been involved in SM of building projects procured by private corporate organisations between 2008 and 2017 in the study area. A second-stage questionnaire was designed to elicit information from the respondents. The quantitative data that were collected were analysed using mean score (MS) analysis and Analysis of variance (ANOVA). Findings: The study found that brainstorming in group meetings (MS = 4.33), interviews with the expert (MS = 3.20) and identification by other stakeholders (MS = 3.00) are the most frequently used SI methods in the study area. It was also found that the use of a questionnaire (MS = 0.87), Delphi method (MS = 0.80) and public hearing (MS = 0.57) was rare for SI in the study area. A further result showed that there was no significant difference in the opinion of project managers on 85% of methods used for SI in the study area irrespective of the procurement method employed. Practical implications: The study examined the methods project managers used for SI on building projects procured by private corporate organisations to advocate for more robust and all-inclusive SI methods. Originality/value: The study empirically examined methods used for SI and correlated them to project performance.